Nerolidol and Farnesol Inhibit Some Cytochrome P450 Activities but Did Not Affect Other Xenobiotic-Metabolizing Enzymes in Rat and Human Hepatic Subcellular Fractions - Špičáková, Alena; Szotáková, Barbora; Dimunová, Diana; Myslivečková, Zuzana; Kubíček, Vladimír; Ambrož, Martin; Lněničková, Kateřina; Krasulová, Kristýna; Anzenbacher, Pavel; Skálová, Lenka (Molecules (Basel, Switzerland), 2017)
Sesquiterpenes, 15-carbon compounds formed from three isoprenoid units, are the main components of plant essential oils. Sesquiterpenes occur in human food, but they are principally taken as components of many folk medicines and dietary supplements. The aim of our study was to test and compare the potential inhibitory effect of acyclic sesquiterpenes, trans-nerolidol, cis-nerolidol and farnesol, on the activities of the main xenobiotic-metabolizing enzymes in rat and human liver in vitro. Rat and human subcellular fractions, relatively specific substrates, corresponding coenzymes and HPLC, spectrophotometric or spectrofluorometric analysis of product formation were used. The results showed significant inhibition of cytochromes P450 (namely CYP1A, CYP2B and CYP3A subfamilies) activities by all tested sesquiterpenes in rat as well as in human hepatic microsomes. On the other hand, all tested sesquiterpenes did not significantly affect the activities of carbonyl-reducing enzymes and conjugation enzymes. The results indicate that acyclic sesquiterpenes might affect CYP1A, CYP2B and CYP3A mediated metabolism of concurrently administered drugs and other xenobiotics. The possible drug-sesquiterpene interactions should be verified in in vivo experiments.
Keywords: Liver; Subcellular Fractions; xenobiotika; Animals; Rats; Kinetics; Inhibitory Concentration 50; játra; Farnesol; subcelulární frakce; lidé; inhibiční koncentrace 50; Sesquiterpenes; seskviterpeny; inhibitory cytochromu P450; Xenobiotics; systém (enzymů) cytochromů P-450; inhibition; drug-metabolizing enzymes; krysa rodu Rattus; nerolidol; zvířata; Cytochrome P-450 Enzyme Inhibitors; kinetika; Cytochrome P-450 Enzyme System; farnesol; Humans